THE IMPACT OF CORPORATE SOCIAL MEDIA ON REVENUE AND PROFIT: AN EXPLORATORY STUDY - J. Zhao, Jensen; Y. Zhao, Sherry (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The growing popularity of social media has fundamentally altered the business ecosystem where companies can no longer solely capture consumers attention via reach; instead, companies must focus on engaging consumers in product and service development and improvement. This exploratory study details how the corporate strategic use of social media relates to corporate revenue and profit among Fortune 500 corporations. The findings indicate that the proper corporate use of social media impacts positively the corporate revenue and profit; whereas the improper corporate use of social media affects negatively the corporate revenue and profit.